Seconding Sinai : the development of Mosaic discourse in Second Temple Judaism - Najman, Hindy (Supplements to the Journal for the study of Judaism, 2003)
This work criticizes the terms "Pseudepigraphy" and "Rewritten Bible", which presuppose conceptions of textual fidelity foreign to ancient Judaism. It develops the concept of a discourse whose creativity and authority depend on repeated returns to the exemplary figure of a founder.